2020
DOI: 10.1111/cup.13866
|View full text |Cite
|
Sign up to set email alerts
|

Discordant anti‐SARS‐CoV‐2 spike protein and RNA staining in cutaneous perniotic lesions suggests endothelial deposition of cleaved spike protein

Abstract: Background: Prior studies have shown the presence of immunohistochemical staining for the SARS-CoV-2 spike protein (SP) in endothelial cells and eccrine epithelium of acral perniosis classified as "COVID toes." Yet, other studies have been unable to detect SARS-CoV-2 RNA in skin biopsies of "COVID toes" by reverse-transcriptase polymerase chain reaction testing. Objective: In order to address these apparently conflicting findings, we compared detection of SARS-CoV-2 SP, through RNA in situ hybridization (ISH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 41 publications
4
53
0
Order By: Relevance
“…Another recent study by Ko et al. demonstrated protein spikes fragments in endothelial cells of cutaneous lesions lacking RNA evidence in ISH suggesting that endothelial incorporated spikes elements rather than the presence of virions may play the pathogenic role in COVID-19 endotheliitis [65] …”
Section: Discussionmentioning
confidence: 99%
“…Another recent study by Ko et al. demonstrated protein spikes fragments in endothelial cells of cutaneous lesions lacking RNA evidence in ISH suggesting that endothelial incorporated spikes elements rather than the presence of virions may play the pathogenic role in COVID-19 endotheliitis [65] …”
Section: Discussionmentioning
confidence: 99%
“…of endothelial infection in deceased COVID-19 patients [30] and called into question the validity of identifying virally-infected cells based on the presence of the SARS-CoV-2 spike protein [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Autopsy studies on COVID-19 patients have suggested the presence of viral particles in the vascular beds of different organs [3,25,26] and others have shown SARS-CoV-2 infection of cultured endothelial cells [27,28] and human blood vessel organoids [29]. In contrast, several studies have failed to find evidence of endothelial infection in deceased COVID-19 patients [30] and called into question the validity of identifying virally-infected cells based on the presence of the SARS-CoV-2 spike protein [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increasing knowledge of COVID‐19‐related skin lesions, few studies have attempted to demonstrate the presence of the virus in skin lesions by real‐time reverse transcriptase polymerase chain reaction (RT‐PCR) 1,2 …”
Section: Case Cutaneous Manifestation Age Sex Medical History Systemic Symptoms Rt‐pcr Nasopharyngeal Sars‐cov‐2 Serology Clinical Evolumentioning
confidence: 99%